Current status and upcoming needs in SME’s in Northern regions of Finland, Norway and Sweden : Technologies, personnel, market and ICT in the business process - Nergård, Henrik; Johansson, Christian; Solvang, Bjørn; Solvang, Wei Deng; Kärkkäinen, Jouko; Pieskä, Sakari; Rättyä, Jani (Luleå tekniska universitet, Innovation och Design, 2012)
The results written in this document comes from a questionnaire that was sent out within the Interreg IV A Nord project Digital integrated Manufacturing. Partners in the project are CENTRIA Research and Development (Lead partner), Finland, Luleå University of Technology, Sweden and Narvik University College, Norway. The project is financed and supported by the European Commission via Europeiska regionala utvecklingsfonden, Länsstyrelsen Norrbotten, Luleå University of Technology, Lapin Liito, CENTRIA Research and Development, Innovasjon Norge, Troms fylkeskommune, Narvik University College and Nordland Fylkeskommune.The projects purpose is to increase the competence and skills of employees in manufacturing Small and Medium Sized Enterprises (SME’s) so that they can improve their global competitiveness within their area of expertise. The project aims to approach this by demonstrating and using new technologies and methods throughout the entire business chain.The Projects primary target groups are the employees within the SME’s in the Interreg IV A Nord area which includes the following region in Norway, Finland and Sweden; Lapplands landskap, Mellersta Österbottens landskap, Norra Österbottens landskap, Norrbottens län, Västerbottens län (Skellefteå, Norsjö, Malå and Sorsele kommuner), Finnmark fylkeskommune, Troms fylkeskommune and Nordland fylkeskommuneThe project contained 4 work packages and this report contains the results from Work Package 1: Current status and upcoming DIM-needs amongst SME’s. One task within this work package was to conduct a questionnaire. The purpose with the questionnaire was to get fundamental knowledge and information from manufacturing companies within the Interreg IV A Nord region regarding the following topics:• General company information and current status• Products and Design and production process• Information and Communication Technologies• Business partner relationships• CompetitionSome conclusions from the questionnaire indicate that companies that answered the ...